ASSESSING THE CONSTRAINS OF WATER SUPPLY FOR IRRIGATION IN HADEJIA VALLEY IRRIGATION PROJECT AREA, JIGAWA STATE NIGERIA. - Garba, Babangida (Machakos University, 2019)
The study assess water supply constrains to irrigated crops in the Hadejia Valley Irrigation Project (HVIP). The HVIP has been identified with declining yields over the years. Different researchers have investigated the reason why soil quality has been the target of many of the researchers. However, findings on the soil have indicated that, the problem is not only on the soils but to water supply. Considering the importance of water supply to irrigated crops, the study investigates into the water supply situation. This study uses random sampling in selecting the sectors and questionnaire survey in the field for data collection. The study show that there is no problem of water availability but the constraints are in the destruction of irrigation infrastructures and the apathy of farmers towards canal maintenance couples with the emergence of a notorious invasive species of plant (typha grass). Simple statistical techniques and descriptive statistics were used in the study. It recommends that H-J.R.B.D.A should provide funds for provision of more irrigation infrastructures and maintenance of existing ones and for research. It also shows the need to encourage Famers Associations to undertake selfhelp activities for the maintenance of the irrigation structures.
Keywords: Assessing; Constraints; Water supply; Irrigation; Project